Profitability and Capital Structure on Firm Value in Indonesian Construction State-Owned Enterprises - Muhammad Alfin Alrasyid; Muhammad Rizki (Entrepreneurship Faculty, Universitas Garut, 2026)
This study aims to examine the effect of profitability and capital structure on the firm value of construction sector State-Owned Enterprises (SOEs) listed on the Indonesia Stock Exchange during the 2015–2024 period. This research employs a quantitative causal associative approach using secondary data collected from four major construction SOEs (PTPP, ADHI, WIKA, and WSKT) over a ten-year observation period. Panel data regression analysis using the Common Effect Model (CEM) is applied to test the proposed relationships. The results reveal that profitability, proxied by Return on Equity (ROE), and capital structure, proxied by Debt to Equity Ratio (DER), do not have a significant effect on firm value, measured by Price to Book Value (PBV), both partially and simultaneously. These findings indicate that the independent variables included in the model have limited explanatory power in determining firm value. This study contributes by highlighting the need to consider additional relevant variables beyond traditional financial ratios in explaining firm value.